Visiting Winifred Loehr in Truckee, CA - Watkins, Howard::::::::: (1978)
Henry Loehr, Winifred Wehe Loehr, Christine Watkins holding Adam Watkins in blue parka On back porch with snow and pine trees in background, 10457 Reynold Way, Truckee, CA